Solid-phase membrane tip extraction combined with liquid chromatography for the determination of azole antifungal drugs in human plasma - Yahaya, Noorfatimah; Sanagi, Mohd Marsin; Nur, Hadi; Wan Ibrahim, Wan Aini; Kamaruzaman, Sazlinda; Aboul-Enein, Hassan Y. (Royal Society of Chemistry, 2014)
A simple and efficient solid-phase membrane tip extraction (SPMTE) was developed using mesoporous silica MCM-41 adsorbent for the determination of three azole antifungal drugs in human plasma prior to high performance liquid chromatography (HPLC). Three azole drugs, namely voriconazole (VRZ), ketoconazole (KTZ) and itraconazole (ITZ), were used as target analytes. The plasma was deproteinized prior to the extraction using methanol–dichloromethane (75 : 25, v/v). Optimized extractions were obtained using the following conditions: conditioning solvent, acetone; extraction time, 15 min; desorption time, 15 min; salt addition, 10% (w/v); pH of sample solution, 8; sample volume, 15 mL and desorption solvent, methanol. A portion of the clean extract (20 μL) was injected into the HPLC-UV system for analysis. Under the optimized conditions, the method demonstrated good linearity with the correlation of determination, r2 ≥ 0.9958 in the concentration range of 60–8000 μg L−1 and good limits of detection in the range of 20–40 μg L−1. The method showed satisfactory precisions with RSDs <16% (n = 3) and high relative recoveries in the range of 82.5–111.0%. The MCM-41-SPMTE method proved to be simple and efficient and requires minimal amounts of organic solvent that supports the green chemistry concept.